Linking Taxonomy and Conservation - Bhatnagar, P. S. (Indian Forester, 2018)
Both taxonomists and conservationists face challenge in their respective areas of work. There is no knowledge about a huge number of species. The Taxonomic Impediment has been defined in the Darwin Declaration in the Global Taxonomic Initiative. The Taxonomic Impediment has been considered central to the conservation/taxonomic problem. The impediment is defined as: â€œThe gaps in knowledge of taxonomic systems, and the reduced impact by not using such knowledge in the management and sustainable use of biodiversity.â€ Conservationists have to work on population or individuals, though they practice habitat conservation as well. Conservationists need taxonomic information in a way that can be used for conservation. It has been hypothesized that Conservation Effort (x) is a function of number of species (n) expressed as f (x) = x n the combined taxonomic and conservation priority is inversely proportional to population size. This could be one way to link taxonomy and conservation.